Macronutrient and sodium content in maize plants under cassava wastewater fertilization - Adriana G. Magalhães; Mario M. Rolim; Anamaria de S. Duarte; Gerônimo F. da Silva; Egídio Bezerra Neto; Elvira M. R. Pedrosa (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to evaluate the content of macronutrients and sodium in corn ( Zea mays) plants as a function of different doses of cassava wastewater and ages of the plants after emergence. The experiment was conducted in a greenhouse in pots with capacity for 25 dm3 of soil, using a 5 × 3 factorial design with four replicates. The studied factors were doses of cassava wastewater: 0; 12.6; 25.2; 50.4; 75.6 m3 ha-1, and plant age: 20, 40 and 52 days after emergence (DAE). Potassium, calcium, magnesium, nitrogen, phosphorus, sodium and sulfur contents were evaluated in leaves and stalks. Nutritional deficiency of calcium was visible at 20 DAE. The increment in cassava wastewater doses increased N, P and K contents in plant shoots, but decreased Ca and Mg absorption. The contents of N, P and K in the leaves and N in stalks at 20 DAE were higher than at 40 and 52 DAE. The highest contents of P and K in the stalks occurred at 40 DAE.